Successive determination of urinary protein and glucose using spectrophotometric sequential injection method - Watla iad Kanchana (2018)
A new sequential injection (SI) system with spectrophotometric detections has been developed for successive determination of protein and glucose. The protein assay is based on ion-association of protein with tetrabromophenolphthalein ethyl ester (TBPE) in the presence of Triton X-100 at pH 3.2. The blue product is monitored for absorbance at 607 nm. For glucose, hydrogen peroxide, generated by the oxidation of glucose in the presence of glucose oxidase immobilized on glass beads packed in a minicolumn, is monitored using iron-catalyzed oxidation reaction of p-anisidine to form a red colored product (520 nm). The SI procedure takes advantage in performing the protein assay during the incubation period for glucose oxidation. Linear ranges were up to 10 mg dL-1human serum albumin (HSA) with a limit of detection (LOD) (3σ) of 0.3 mg dL-1, and up to 12.5 mg dL-1glucose with LOD of 0.08 mg dL-1. R.S.D.s (n = 11) were 2.7% and 2.5% (for 1 mg dL-1and 5 mg dL-1HSA) and 1.4% (9 mg dL-1glucose). Sample throughput for the whole assay of both protein and glucose is 6 h-1. The automated system has been demonstrated for the successive assay of protein and glucose in urine samples taken from diabetic disease patients, with good agreement with the other methods. This developed SI system is an alternative automation for screening for diabetic diagnosis. © 2007.